2014
DOI: 10.1021/ci5003697
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Potential Anticancer Agents from African Medicinal Plants

Abstract: Naturally occurring anticancer compounds represent about half of the chemotherapeutic drugs which have been put in the market against cancer until date. Computer-based or in silico virtual screening methods are often used in lead/hit discovery protocols. In this study, the "drug-likeness" of ~400 compounds from African medicinal plants that have shown in vitro and/or in vivo anticancer, cytotoxic, and antiproliferative activities has been explored. To verify potential binding to anticancer drug targets, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 105 publications
0
55
0
Order By: Relevance
“…Studies in silico have been published for Ebola VP35 and VP40, and, very recently, a machine learning method that uses Bayesian and Support Vector Machine (SVM) algorithms was proposed by Ekin et al [25] for the identification of novel Ebola inhibitors from already reported antiviral data. Over the past decade, there has been significant interest in the exploitation of phytochemicals for pharmaceutical use, many of which have antiviral or anticancer activities; a few studies have focused on the potential of phytochemicals as possible parental compounds for the treatment of haemorrhagic fever [34,35]. Kolokoltsov et al demonstrated that a cocktail of genistein and tyrphostin AG1478, both of which are kinase inhibitors, forms a broad spectrum antiviral agent that can be used for the treatment of both arenavirus and filovirus haemorrhagic fevers [36].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in silico have been published for Ebola VP35 and VP40, and, very recently, a machine learning method that uses Bayesian and Support Vector Machine (SVM) algorithms was proposed by Ekin et al [25] for the identification of novel Ebola inhibitors from already reported antiviral data. Over the past decade, there has been significant interest in the exploitation of phytochemicals for pharmaceutical use, many of which have antiviral or anticancer activities; a few studies have focused on the potential of phytochemicals as possible parental compounds for the treatment of haemorrhagic fever [34,35]. Kolokoltsov et al demonstrated that a cocktail of genistein and tyrphostin AG1478, both of which are kinase inhibitors, forms a broad spectrum antiviral agent that can be used for the treatment of both arenavirus and filovirus haemorrhagic fevers [36].…”
Section: Introductionmentioning
confidence: 99%
“…The docking protocol explained in experimental section gave an rmsd of 2.09 Å which is within the recommended range and hence was implemented in this study (Fig 2) [36]. …”
Section: Resultsmentioning
confidence: 99%
“…The crystal structures of the bacteria DNA gyrase (PDB code: 1KZN) with its cocrystallized inhibitor (chlorobiocin) were downloaded from RCSB protein data bank [35]. The enzyme-inhibitor complexes were prepared according to standard for use in docking calculation [36]. Both the ligands and protein were energy minimized to a gradient of 0.001 kcal/mol using Merck Molecular (MMFF94) Force field [37].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, within last four to five years, a huge number of public repositories have been established for medicinal plants and their derived phytochemicals. The list includes, but is not limited to MPD3 [21], Phytochemica [22], SerpentinaDB [23], FERN Ethnomedicinal Plant Database [24], Naturally Occurring Plant-based Anti-Cancer Compound-Activity-Target Database (NPACT) [25], SuperNatural [26], Herb Ingredients' Targets (HIT) [27], Cancer Resource-dataset of compound-target interactions [13], Traditional Chinese medicine database (TCMD) [28], China natural products database (CNPD) [29], Chinese herb constituents database (CHCD) [30], Bioactive plant compounds database (BPCD) [30], Nuclei of Bioassays, Ecophysiology and Biosynthesis of Natural Products Database (NuBBEDB) [31,32], Northern African Natural Products Database (NANPDB) [33], Highly potent and diverse natural product library from African medicinal plants (AfroDb) [34], Molecular modeling of potential anticancer agents from African medicinal plants (AfroCancer) [35], Database of Volatile Organic Compounds in Cancer (VOCC) [36], and Nutrient Use Efficiency (NtUE) Web-Resource [37]. However, a similar comprehensive database for Uttarakhand medicinal plants is still not available despite a recent database development by the ENVIS center on Forestry with very limited scope and information.…”
Section: Introductionmentioning
confidence: 99%